A priority based on min-min algorithm for reducing make span task scheduling in cloud computing - Obaid, Abdulrahman Mohammed Hussein; Pani, Santosh Kumar; Pattnaik, Prasant Kumar (International Journal of Engineering and Technology, 2018)
This paper proposes a two-phase technique for task scheduling which works on third-party broker. The priority algorithm is executed by selecting the task that has the highest priority. However, if more than one task has the same priority; it goes to second phase to execute the traditional Min-Min algorithm. Experiments are conducted by considering random tasks in order to compare the performance of the pro-posed algorithm with the Min-Min algorithm. The recorded experimental outcomes indicate that the proposed technique is given 10% better results as compared to the traditional Min-Min algorithm.